Systematization of perioperative nursing care in patients undergoing percutaneous transluminal coronary angioplasty (Research, Society and Development, 2022)
The Systematization of Perioperative Nursing Care, seeks to ensure the planning of care according to the individual needs of each patient in pre, intra, and postoperative conditions and ensure comprehensive, individualized, effective and duly recorded care, in order to increase standards of safe nursing care. Objective: To analyze the epidemiological profile of patients undergoing percutaneous transluminal coronary angioplasty and to evaluate nursing care for this population. Method: This research is an integrative literature review. Results: The relevance of SAEP in the care of patients undergoing percutaneous transluminal coronary angioplasty was verified. Conclusion: The Systematization of Perioperative Nursing Care guarantees the planning and care in an integral, holistic and individualized way, ensuring greater well-being and protection for clients, contributing to a better quality of life after percutaneous coronary intervention.